Geochemistry of a paleo-oxbow lake sediments and its implications for the late Holocene extreme overbank flooding history of the Yellow River within the Zoige Basin, NE Tibetan Plateau - Wang, Shuo; Wang, Ninglian; Zhang, Yuzhu; Huang, Chang; Zhu, Yan; Xiao, Qili; Chen, Dou; Wang, Haoyu; Ming, Yisen; Huang, Xiaoling; Wang, Sikai (Frontiers in Earth Science, 2023)
Paleo-oxbow lake sediments can provide archives to reconstruct paleo-channel evolution and flooding history of the river. Multi-proxy approaches including detailed sediment stratigraphy, sedimentology and geochemistry have been implemented in a high-resolution sedimentary section of paleo-oxbow lake of the Yellow River within the Zoige Basin on the NE Tibetan Plateau, to reconstruct regional environmental changes and extreme overbank flooding history. Our results suggest that not only traditional sedimentological proxies, but also chemical elements can be applied in defining sequences with different genetic types, especially the paleoflood deposits in the paleo-oxbow profile. Two units of late-Holocence extreme overbank flooding deposits (OFDs) are identified in terms of the significantly higher proportions of sand, high contents of SiO2, Na2O, Ba, low contents of Al2O3, Fe2O3, MgO, K2O, Ti, Rb and high values of Zr/Fe, Zr/Rb ratios. These extraordinary flood events within the Zoige Basin were dated back to 2960 ± 240–2870 ± 270 a and 1840 ± 200–1700 ± 160 a, in response to the mid-Holocene climatic optimum to the late Holocene and the Dark Age Cold Period (DACP). And the strong rainfall caused by the abnormal atmospheric circulation during the period of climate transition and abrupt change may led to the frequent occurrence of extreme flood events in the source region of the Yellow River. These findings are important for understanding the response of regional fluvial system to high climatic instability and provide a new perspective for us to analyze the risk of flood disasters on the Tibet Plateau under the background of climate change.